The effectiveness compensation & benefits and performance appraisal on employee engagement among employees in Felda Global Ventures Holdings Berhad (FGVHB) - Ramdzan, Radzi (2018)
The study aims to examine the relationship between compensation & benefits and performance appraisal to the employee engagement among employees in Felda Global Ventures Holdings Berhad (FGVHB). The questionnaire was distributed to approximately 400 randomly selected employees under Cluster and Division in FGVHB, of which a total of 385 responses were obtained. However only 377 questionnaires were completed and used for the analysis of this study. The data were analysed analyzed using Statistical Package for the Social Sciences (SPSS) version 22.0. The statistical method of Pearson correlation was employed to determine the existence of any relationships between compensation & benefits and performance appraisal with employee engagement. Regression analysis was conducted to examine which independent variables predict the Employee Engagement and Cronbach Alpha was used for further illustrate the reliability test. Throughout the statistical analysis of correlation analysis, it is found that there is a significant relationship between the two variables, which are compensation & benefits and performance appraisal with dependent variable: Employee Engagement. This study will help for FGVHB to improve on its current employee engagement initiatives, also further enhance and develop more engagement initiatives to improve engagement level in FGVHB. Likewise, limitation and recommendation for future research direction were also deliberated in this study.